Volatile Compounds Content and Sensory Profile of Katuk (Sauropus androgynus) Leaves After Household Scale Heating - Ardiansyah, Ardiansyah; Advisa, Daivy Atiya; Asiah, Nurul; David, Wahyudi; Kusbiantoro, Bram; Handoko, Dody Dwi (agriTECH, 2024)
Katuk (Sauropus androgynus) is an indigenous Indonesian plant, and the leaves are often consumed as fresh or processed vegetables. Despite its potential, there are no reports on the volatile compounds content and sensory profile of Katuk leaves after being processed using household scale heating. Therefore, this study aimed to determine the volatile compounds content and sensory profiles of Katuk leaves after household scale heating (steaming and boiling). The extraction of constituents was carried out using the headspace-solid phase microextraction method, followed by identification with gas chromatography-mass spectroscopy. The sensory profile analysis was performed using the free choice profiling method with untrained panelists. The analysis results showed the presence of 16 volatile compounds derived from 7 groups, including aldehydes (5 compounds), alcohol (3 compounds), other components (3 compounds), ketones (2 compounds), as well as benzene, terpenoids, and esters (1 compound). The dominant compounds found in fresh Katuk leaves were alcohol [(Z)-3-hexene-1-ol]. Meanwhile, aldehydes (benzaldehyde, nonanal, benzeneacetaldehyde, and (E)-2-pentenal) and alcohol (1-Heptanol and Nerolidol) were dominant in the steamed samples, with benzene (naphthalene) being predominantly found in the boiled samples. The sensory profile analysis results showed that fresh Katuk leaves had a grassy and earthy aroma with a grassy flavor, while the boiled samples had a smooth and juicy texture. The dominant attributes found in steamed Katuk leaves included moist, tender, and tasteless. Based on these findings, household scale heating could modify the composition of volatile compounds, thereby affecting the sensory profile. The results obtained were expected to serve as a foundation for the processing of Katuk leaves at both industry and household levels.